Huanglian Jiedu Decoction for treatment of multiple myeloma: A protocol for a systematic review and meta-analysis. Issue 51 (18th December 2020) - An, Na; Li, Yiwei; Huang, Xilian; Chen, Can; Xie, Yaping
Abstract: Background: Multiple myeloma can lead to lots of clinical problems including pain, fatigue, anemia, infections, renal failure, and so on. Huanglian Jiedu Decoction is a common conservative treatment for this disease in China. Therefore, we conducted a systematic review and meta-analysis to explore the efficacy of Huanglian Jiedu Decoction in the treatment of multiple myeloma. Methods: A systematic literature search for studies will be performed in 8 databases, including PubMed, Web of Science, Embase, the Cochrane library, ClinicalTrials.gov databases, Chinese National Knowledge Infrastructure Database, Wanfang database, and VIP database. The methodological quality of the included studies using the risk bias assessment tool of Cochrane. And the level of evidence for results is assessed by the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method. Statistical analysis is conducted with Revman 5.3. Results: This systematic review and meta-analysis will provide a synthesis of existed evidences for Huanglian Jiedu Decoction on multiple myeloma. Conclusion: The conclusion of this study will provide evidence to assess effectiveness of Huanglian Jiedu Decoction on multiple myeloma, which can further guide clinical decision-making. INPLASY registration number: INPLASY202060094